The Use of Flipgrid in Improving Secondary School Teachers’ Motivation and Confidence in Speaking English - Eva Rosita; Sisilia Halimi (JEELS (Journal of English Education and Linguistics Studies), 2023)
This case study sought to determine the effectiveness of Flipgrid in enhancing the speaking abilities of 20 secondary school teachers representing a variety of subject disciplines. After recording three video monologues and writing reflective journals about their practice experience, all participants responded to questionnaire and interview to express how Flipgrid affected their motivation and self-confidence in speaking English along with their perception of the platform. The interview data was analyzed using Nvivo software by utilizing In Vivo coding. Then, the analysis result was triangulated with the questionnaire. It was concluded that Flipgrid was suitable for participants with English basic proficiency. It also assisted those with intermediate and advanced levels to practice speaking English independently. All participants were motivated due to the excitement, enjoyment, challenge, and self-assurance to speak more effectively. It affected their confidence because their pronunciation, vocabulary, fluency, and grammar improved. Despite minor obstacles in operating Flipgrid, it was considered effective due to its accessibility, helpfulness, and friendliness. This research revealed that using Flipgrid and combining it with face-to-face learning would be a good way to practice speaking English and in future studies, the efficacy of these two strategies would be worth investigated.